2023
DOI: 10.2147/clep.s443473
|View full text |Cite
|
Sign up to set email alerts
|

The Danish Atrial Fibrillation Registry: A Multidisciplinary National Pragmatic Initiative for Monitoring and Supporting Quality of Care Based on Data Retrieved from Administrative Registries

Lars Frost,
Albert Joensen,
Ulla Dam-Schmidt
et al.

Abstract: The Danish Atrial Fibrillation (AF) Registry monitors and supports improvement of quality of care for all AF patients in Denmark. This report describes the registry's administrative and organizational structure, data sources, data flow, data analyses, annual reporting, and feedback between the registry, clinicians, and the administrative system. We also report the selection process of the quality indicators and the temporal trends in results from 2017-2021. Methods and Results:The Danish AF Registry aims for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Estimates of the lifetime risk of complications after atrial fibrillation indicate the burden of the different complications, and such information may be essential to facilitate prioritisation and development of preventive efforts against complications, prediction of complications, and management of health policy. In Denmark, more than 85% of patients with atrial fibrillation initiate oral anticoagulation, and the one year and two year persistence are both above 85% 38. Despite a high rate of anticoagulation treatment, we observed that stroke risk remains a very important problem after atrial fibrillation.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Estimates of the lifetime risk of complications after atrial fibrillation indicate the burden of the different complications, and such information may be essential to facilitate prioritisation and development of preventive efforts against complications, prediction of complications, and management of health policy. In Denmark, more than 85% of patients with atrial fibrillation initiate oral anticoagulation, and the one year and two year persistence are both above 85% 38. Despite a high rate of anticoagulation treatment, we observed that stroke risk remains a very important problem after atrial fibrillation.…”
Section: Discussionmentioning
confidence: 67%
“…In Denmark, more than 85% of patients with atrial fibrillation initiate oral anticoagulation, and the one year and two year persistence are both above 85%. 38 Despite a high rate of anticoagulation treatment, we observed that stroke risk remains a very important problem after atrial fibrillation. These findings underscore the need for treatments to further decrease stroke risk.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations